FACTORS THAT AFFECT JOB SATISFACTION OF EMPLOYEES AT PT. MITRA SUKSES INTI PERKASA PEKANBARU - Dianita, Nana; Azhari, Riko (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The purpose of this study to determine factors that affect job satisfaction of employees at PT. Mitra Sukses Inti Perkasa Pekanbaru. The sample in this research is all employees at PT. Mitra Sukses Inti Perkasa Pekanbaru totaling 48 people. Sampling was conducted using a sample saturated. (Sugiyono, 2010: 96) The data analysis is done by using validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression, R2 test, F test, t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). The final conclusion of the study on the variables factor employee and occupational factors on employee job satisfaction can be seen from Table F value obtained for F (0,05) (45) = 3,20, while F count on the F test is obtained from the data processed by 20,510, meaning F count = 20,510 > 3,20, then Ho is rejected and Ha received means there is the factor employee and occupational factors on employee job satisfaction at PT. Mitra Sukses Inti Perkasa Pekanbaru. From the results of the t test that most affect job satisfaction at PT. Mitra Sukses Inti Perkasa Pekanbaru is the occupational factors with t value 4,120 > 2.013, then Ho is rejected and Ha accepted, meaning the partial occupational factors positive and significant impact on job satisfaction, while the results of the regression equation linear is Y = 6,477 + 0,168X1 + 0,513X2. Thus meaning any change in factor employee and occupational factors, whether positive or negative will be amended also on employee job satisfaction at PT. Mitra Sukses Inti Perkasa Pekanbaru